Sądownictwo diecezji włocławskiej : historia i teraźniejszość : na tle rozwoju sądownictwa kościelnego w Polsce - Grzęźlikowski, Janusz (Ius Matrimoniale, 2004)
Development and organization of the Włocławek Diocese’s judiciary are closely linked to transformations and changes in organization and territory of the <span style="background-color: #ffffff; color: #000000; font-family: " noto sans",arial,helvetica,sans-serif; font-size: 14px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">Włocławek Diocese, initially named Kruszwica Diocese (till 1123), Kujawy-Pomerania (1123-1818), Kujawy-Kalisz (1818-1925) and finally <span style="background-color: #ffffff; color: #000000; font-family: " noto sans",arial,helvetica,sans-serif; font-size: 14px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">Włocławek (since 1925). The beginnings of the <span style="background-color: #ffffff; color: #000000; font-family: " noto sans",arial,helvetica,sans-serif; font-size: 14px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">Włocławek oficjalat (court) date back to the 13th century. It supervised the Kujawy part of the diocese. In 1918 it transformed into the <span style="background-color: #ffffff; color: #000000; font-family: " noto sans",arial,helvetica,sans-serif; font-size: 14px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">Włocławek Bishop Court. The <span style="background-color: #ffffff; color: #000000; font-family: " noto sans",arial,helvetica,sans-serif; font-size: 14px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">Włocławek Diocese should be identified as the first one in Poland which since 1289 has had a foralny oficjalat (district court) for the Pomeranian section of the diocese, and later other district oficjalat (court) in Bydgoszcz, Wieluń, Piotrków Trybunalski and Kalisz, which depended on changes in the diocese’s borders. The Pomeranian oficjalat (court), initially a foralny (district) one, in 15th century transformed into a general one, and after the borders’ change in 1818 there were two general oficjalaty (courts): the Włocławek one and the Kalisz one. he final changes in the organization of the judiciary in the Włocławek diocese were caused by introduction of the Canon Law Code from 1917 and reorganization of the administrative division of the diocese in 1925. These changes resulted in one tribunal operating in the Włocławek Diocese, which spreads its jurisdiction on the entire diocese.